Painful leg in a diabetic patient: an unusual cause (pyomyositis) - Sanjay Bhat; Kalyan Dutt; Khalid Javid Bhat (SpringerOpen, 2014)
Pyomyositis, a rare condition can involve perfectly healthy individuals but is generally a disease of immunocompromised like diabetic patients. Probably, the result of transient bacteraemia characteristically involve muscles of lower limbs. Clinically to begin with, can mimic other non-infective musculoskeletal disease which often result in the delay of diagnosis.